The atlas of endangered species - Burton, John A. (New York : Macmillan ; Toronto : Maxwell Macmillan Canada, 1991)
Describes the various animals and plants throughout the world whose survival is being threatened and the steps being taken to save them fro m extinction.
Includes bibliographical references (p. 250) and index.
Keywords: Endangered species -- Juvenile literature; Endangered plants -- Juvenile literature; Nature conservation -- Juvenile literature; Rare animals; Rare plants; Wildlife conservation; Environmental protection